Kedudukan Hukum Ibukota Kabupaten Setelah Dimekarkan Menjadi Pemerintah Kota - Alinapia, Alinapia (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
The problems of this research are: firstly how is the law position of district capital city South Tapanuli after separated from Sidimpuan city? Secondly, what are the law effects of between double capital cities and two autonomy areas? In this research, it used law research method, with collected the data based on interview and documentation. It was analysis with hypotheses technique inductively and deductively, therefore it found that the position the main capital city of district South Tapanuli after separated from Padangsidimpuan is Padangsidimpuan. Although in constitutions of establishment Padang Lawas in 2007, it is determined Sipirok as the capital city, but it is realization in 2014. Meanwhile the effects of law double capitals, in generally can disturb the continuity of both government and especially it will happen discrepancy, minus work ethic, there is the classification of society, outdated of tradition â€œdalihan natoluâ€ and easily to provoked both two government.